Anti-aging acrylic resin waterproof coating and preparation method thereof
By adding benzotriazole and 4-pyrazolecarboxylic acid modified nano-oxidized particles to the acrylic resin waterproof coating, the problem of poor aging performance of the coating under ultraviolet radiation is solved, and the aging resistance is achieved, making it suitable for exterior walls in areas with strong ultraviolet rays.
Patent Information
- Application Number
- CN202510338558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing acrylic resin waterproof coatings have poor aging performance under long-term ultraviolet radiation, and are especially effective when used in areas with strong ultraviolet rays.
By adding the ultraviolet absorber benzotriazole to the methacrylic acid copolymer and using nano-oxidized particles modified with 4-pyrazole carboxylic acid as filler, the ultraviolet absorption capacity and aging resistance of the coating are improved.
It significantly improves the aging resistance of acrylic waterproof coatings and can be suitable for exterior walls in areas with strong ultraviolet rays.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an aging-resistant acrylic resin waterproof coating and a preparation method thereof. Background Art
[0002] Paint is a type of liquid that is applied to the surface of an object and forms a thin film under certain conditions to play a protective, decorative and specific role. The most basic function of waterproof paint is waterproofing. For waterproof paints used in different occasions, other functions need to be added to increase their service life. For example, for waterproof paints used on exterior walls, they are required to have high aging resistance; for indoor waterproof paints, environmental issues need to be considered.
[0003] Acrylic resin has many excellent properties, such as light color, gloss retention, color retention, weather resistance, corrosion resistance, and aging resistance. The waterproof coating prepared with acrylic resin as the base material has good aging resistance. However, when the waterproof coating is used for exterior walls, long-term exposure to ultraviolet radiation will also lead to poor aging resistance of the waterproof coating.
[0004] In the prior art, antioxidant and UV-absorbing fillers are usually added to waterproof coatings to reduce the damage of ultraviolet rays to acrylic resins, thereby improving the aging resistance of acrylic resin-based waterproof coatings. However, the effect is still limited, especially when used in areas with strong ultraviolet rays. Summary of the invention
[0005] The purpose of the present invention is to provide an aging-resistant acrylic resin waterproof coating and a preparation method thereof, so as to improve the aging-resistant performance of the acrylic resin waterproof coating.
[0006] The present invention is achieved through the following technical solutions: An aging-resistant acrylic resin waterproof coating comprises the following components in parts by weight: 100 parts of modified acrylic resin emulsion, 30-40 parts of filler, 5-8 parts of film former, 2-3 parts of thickener, 2-3 parts of dispersant; The modified acrylic resin emulsion comprises the following components by weight: 100 parts of dispersion, 30-35 parts of methacrylic acid copolymer, 10-12 parts of benzotriazole; The filler is nano-oxide particles modified by 4-pyrazolecarboxylic acid, and the nano-oxide particles include at least one of nano-zinc oxide and nano-titanium dioxide.
[0007] The present invention is to modify the base material acrylic resin and filler in the existing acrylic resin waterproof coating. The acrylic resin is specifically a methacrylic acid copolymer, and benzotriazole is added to the methacrylic acid copolymer. Benzotriazole is an ultraviolet absorber and can be dissolved in the dispersion. Since the methacrylic acid copolymer contains carbonyl groups, the carbonyl groups in the methacrylic acid copolymer are lost under long-term ultraviolet rays, resulting in aging of the coating. The more carbonyl groups in the methacrylic acid copolymer are lost, the faster the coating ages, and the performance of the coating deteriorates after aging.
[0008] The modified acrylic resin emulsion of the present invention contains a methacrylic acid copolymer and benzotriazole, which can absorb ultraviolet rays, and can almost completely absorb ultraviolet light of 290-390 nm, and can transmit visible light of 420 nm; therefore, benzotriazole can reduce the damage of ultraviolet light to the carbonyl group in the methacrylic acid copolymer, and improve the aging resistance of the coating to a certain extent.
[0009] The filler of the present invention is improved on the basis of existing nano-oxide particles capable of absorbing ultraviolet rays. Specifically, nano-oxide particles modified with 4-pyrazolecarboxylic acid are used. The 4-pyrazolecarboxylic acid contains a carboxyl group (-COOH) and is weakly acidic. Under aqueous conditions, the 4-pyrazolecarboxylic acid will ionize H+ to form a negative charge on the surface of the 4-pyrazolecarboxylic acid. The surface of the nano-oxide particles usually carries a positive charge, and an adsorption effect is formed between the positive charge and the negative charge. In addition, the molecular structure of the 4-pyrazolecarboxylic acid is a five-membered ring, which contains two nitrogen atoms and three carbon atoms. One of the carbon atoms in the 4-pyrazolecarboxylic acid ring is connected to the adjacent nitrogen atom through a double bond, and the electrons in the entire ring system can flow freely between the carbon and nitrogen atoms, thereby forming a conjugated structure. The conjugated structure allows the 4-pyrazolecarboxylic acid to form a bonding reaction with the surface of zinc oxide, and finally, a 4-pyrazolecarboxylic acid modified layer is formed on the surface of the nano-oxide particles. The 4-pyrazolecarboxylic acid modified layer can improve the dispersibility and surface activity of the nano-oxide particles, thereby improving the ultraviolet light absorption ability of the nano-oxide particles.
[0010] In summary, the present invention can improve the aging resistance of acrylic resin waterproof coating.
[0011] The present invention improves the acrylic resin and filler in the existing acrylic resin waterproof coating. On the one hand, ultraviolet absorber benzotriazole is added to the methacrylic acid copolymer to reduce the loss of carbonyl groups in the methacrylic acid copolymer under ultraviolet conditions. On the other hand, 4-pyrazolecarboxylic acid is used to modify nano-oxidation particles, and a 4-pyrazolecarboxylic acid modification layer is formed on the surface of the nano-oxidation particles. The 4-pyrazolecarboxylic acid modification layer can improve the dispersibility and surface activity of the nano-oxidation particles, thereby improving the ultraviolet light absorption energy of the nano-oxidation particles. Therefore, the ultraviolet absorption capacity of the acrylic resin waterproof coating of the present invention can be greatly improved, the damage of the carbonyl groups in the methacrylic acid copolymer is greatly reduced, and the aging resistance of the acrylic resin waterproof coating is improved, so that the acrylic resin waterproof coating can be suitable for exterior walls in areas with strong ultraviolet rays.
[0012] In a preferred embodiment, the preparation process of the modified acrylic resin emulsion is: Add the methacrylic acid copolymer into the dispersion and mix well. Then add benzotriazole into the solution and disperse it by ultrasonic for 20-30 minutes.
[0013] In a preferred embodiment, the dispersion containing the methacrylic acid copolymer is heated to 40-45° C. before adding benzotriazole, and the temperature is maintained at 40-45° C. during ultrasonic dispersion, which can improve the binding force between benzotriazole and the methacrylic acid copolymer and facilitate the protection of the carbonyl group in the methacrylic acid copolymer by benzotriazole.
[0014] In a preferred embodiment, benzotriazole is pretreated by ball milling, and the benzotriazole is ground by ball milling, which can reduce the particle size of benzotriazole and increase the specific surface area of benzotriazole, so that benzotriazole can be better dispersed in the methacrylic acid copolymer. The benzotriazole with refined particle size not only has better dispersibility, but also can improve its binding force with the methacrylic acid copolymer, further improving the protective effect of the modified benzotriazole on the methacrylic acid copolymer.
[0015] In a preferred embodiment, the preparation process of the filler is: 4-pyrazolecarboxylic acid is added to 85% ethanol, and ultrasonic dispersion is performed for 20-30 minutes. Then, nano-oxide particles are added to the solution, and ultrasonic dispersion is performed for 40-60 minutes. Then, the ethanol is volatilized and air-dried to obtain a filler.
[0016] In a preferred embodiment, the weight ratio of ethanol, nano-oxidation particles and 4-pyrazolecarboxylic acid is (10-15): (8-12): (3-5).
[0017] In a preferred embodiment, the weight ratio of ethanol, nano-oxidation particles and 4-pyrazolecarboxylic acid is 15:10:(3-5).
[0018] In a preferred embodiment, the nano-oxide particles are first pretreated: The nano-oxide particles are dispersed in a sodium chloride solution, wet-milled, and dried.
[0019] A method for preparing an acrylic resin waterproof coating comprises the following steps: S1, adding the modified acrylic resin emulsion into a stirring tank and stirring, then sequentially adding a dispersant and a film-forming agent, stirring, so that the dispersant and the film-forming agent are evenly dispersed in the modified acrylic resin emulsion; S2, add filler and continue stirring at high speed to make all components dispersed evenly; S3. Add a thickener to adjust the consistency to obtain an acrylic resin waterproof coating.
[0020] In a preferred embodiment, in step S1, the stirring speed is 500-600 r.min -1 In step S2, the stirring speed is 1500-1600 r.min -1 .
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention improves the acrylic resin and filler in the existing acrylic resin waterproof coating. On the one hand, ultraviolet absorber benzotriazole is added to the methacrylic acid copolymer to reduce the loss of carbonyl groups in the methacrylic acid copolymer under ultraviolet conditions. On the other hand, 4-pyrazolecarboxylic acid is used to modify nano-oxidation particles, and a 4-pyrazolecarboxylic acid modification layer is formed on the surface of the nano-oxidation particles. The 4-pyrazolecarboxylic acid modification layer can improve the dispersibility and surface activity of the nano-oxidation particles, thereby improving the ultraviolet light absorption energy of the nano-oxidation particles. Therefore, the ultraviolet absorption capacity of the acrylic resin waterproof coating of the present invention can be greatly improved, the damage of the carbonyl groups in the methacrylic acid copolymer is greatly reduced, and the aging resistance of the acrylic resin waterproof coating is improved, so that the acrylic resin waterproof coating can be suitable for exterior walls in areas with strong ultraviolet rays. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The schematic implementation mode of the present invention and its description are only used to explain the present invention and are not intended to limit the present invention. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0023] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.
[0024] In order to improve the aging resistance of acrylic resin waterproof coating so that it can be better applied to exterior walls, this embodiment provides an aging-resistant acrylic resin waterproof coating, comprising the following components in parts by weight: 100 parts of modified acrylic resin emulsion, 30-40 parts of filler, 5-8 parts of film former, 2-3 parts of thickener, and 2-3 parts of dispersant.
[0025] The modified acrylic resin emulsion includes the following components in parts by weight: 100 parts of dispersion liquid, 30-35 parts of methacrylic acid copolymer, and 10-12 parts of benzotriazole. The benzotriazole and methacrylic acid copolymer are both commercially available, and the methacrylic acid copolymer is specifically methacrylic acid copolymer type B. The dispersion liquid can specifically be isopropanol, ethyl acetate, and toluene.
[0026] The preparation process of modified acrylic resin emulsion is: Add the methacrylic acid copolymer into the dispersion and mix well. Then add benzotriazole into the solution and disperse it by ultrasonic for 20-30 minutes.
[0027] In a preferred case, the dispersion containing the methacrylic acid copolymer is heated to 40-45°C before adding benzotriazole; and the temperature is maintained at 40-45°C during the ultrasonic dispersion process, which can improve the binding force between benzotriazole and the methacrylic acid copolymer and facilitate the protection of the carbonyl group in the methacrylic acid copolymer by benzotriazole.
[0028] In a preferred embodiment, benzotriazole is pretreated by ball milling.
[0029] The filler is nano-oxide particles modified by 4-pyrazolecarboxylic acid, and the nano-oxide particles include at least one of nano-zinc oxide and nano-titanium dioxide.
[0030] The preparation process of the filler is: Add 4-pyrazolecarboxylic acid to 85% ethanol, ultrasonically disperse for 20-30 minutes, then add nano-oxidation particles to the solution, ultrasonically disperse for 40-60 minutes; then evaporate the ethanol and air-dry to obtain a filler. The weight ratio of ethanol, nano-oxidation particles and 4-pyrazolecarboxylic acid is (10-15): (8-12): (3-5), preferably, the weight ratio of ethanol, nano-oxidation particles and 4-pyrazolecarboxylic acid is 15:10: (3-5).
[0031] In a preferred case, the nano-oxide particles are first pretreated: the nano-oxide particles are dispersed in a sodium chloride solution, wet-milled, and dried.
[0032] Wherein, the dispersant is Allnex6208 dispersant.
[0033] The thickener is any one of hydroxypropyl methylcellulose and hydroxyethyl cellulose.
[0034] Wherein, the film-forming agent is any one of dodecyl alcohol ester and hexanediol butyl ether acetate.
[0035] The preparation method of the acrylic resin waterproof coating of the present embodiment comprises the following steps: S1. Add the modified acrylic resin emulsion into the stirring tank and stir, then add the dispersant and film-forming agent in sequence, stir at a speed of 600 r.min. -1 ; Make the dispersant and film-forming agent uniformly dispersed in the modified acrylic resin emulsion; S2, add filler, continue stirring at high stirring speed, stirring speed is 1500 r.min -1 ; Make each component dispersed evenly; S3. Add a thickener to adjust the consistency to about 10 cm to obtain an acrylic resin waterproof coating.
[0036] In this embodiment, both the base acrylic resin and the filler in the existing acrylic resin waterproof coating are improved; on the one hand, the ultraviolet absorber benzotriazole is added to the methacrylic acid copolymer to reduce the loss of carbonyl groups in the methacrylic acid copolymer under ultraviolet conditions; on the other hand, 4-pyrazolecarboxylic acid is used to modify the nano-oxide particles, and a 4-pyrazolecarboxylic acid modification layer is formed on the surface of the nano-oxide particles. The 4-pyrazolecarboxylic acid modification layer can improve the dispersibility and surface activity of the nano-oxide particles, thereby improving the ultraviolet light absorption ability of the nano-oxide particles. Therefore, the ultraviolet absorption capacity of the acrylic resin waterproof coating of this embodiment can be greatly improved, and the damage to the carbonyl groups in the methacrylic acid copolymer is greatly reduced, thereby improving the aging resistance of the acrylic resin waterproof coating, so that it can be suitable for exterior walls in areas with strong ultraviolet rays.
[0037] In order to better illustrate the technical effect of this embodiment, the following case is used for illustration.
[0038] Embodiment 1: An aging-resistant acrylic resin waterproof coating, comprising the following components in parts by weight: 100 parts of modified acrylic resin emulsion, 40 parts of filler, 8 parts of film-forming agent, 3 parts of thickener, and 3 parts of dispersant.
[0039] Wherein, the preparation process of modified acrylic resin emulsion is as follows: The benzotriazole was pretreated by ball milling to obtain modified benzotriazole; 35 parts of methacrylic acid copolymer type B were added to 100 parts of toluene and mixed at 45° C., and then 12 parts of the modified benzotriazole were added to the solution and ultrasonically dispersed for 30 minutes.
[0040] The preparation process of the filler is as follows: 4-pyrazolecarboxylic acid was added to 85% ethanol, ultrasonically dispersed for 30 minutes, and then nano zinc oxide was added to the solution, ultrasonically dispersed for 60 minutes; then the ethanol was volatilized and air-dried to obtain a filler. The weight ratio of ethanol, nano zinc oxide and 4-pyrazolecarboxylic acid was 15:10:5.
[0041] Among them, the dispersant is Allnex6208 dispersant; the thickener is hydroxypropyl methylcellulose; and the film-forming agent is dodecyl alcohol ester.
[0042] Embodiment 2: This embodiment is based on Embodiment 1, and differs from Embodiment 1 in that: The nano zinc oxide is first pretreated: the nano zinc oxide is dispersed in a saturated sodium chloride solution, wet ball milled, and dried; wherein the nano zinc oxide and the sodium chloride solution are mixed in equal proportions.
[0043] Wherein, the preparation process of modified acrylic resin emulsion is as follows: The benzotriazole was pretreated by ball milling to obtain modified benzotriazole; 35 parts of methacrylic acid copolymer type B were added to 100 parts of ethyl acetate and mixed at 45° C., and then 12 parts of the modified benzotriazole were added to the solution and ultrasonically dispersed for 30 minutes.
[0044] Embodiment 3: This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the dosage of each component is different, specifically: An aging-resistant acrylic resin waterproof coating, comprising the following components in parts by weight: 100 parts of modified acrylic resin emulsion, 30 parts of filler, 5 parts of film former, 2 parts of thickener and 2 parts of dispersant.
[0045] Wherein, the preparation process of modified acrylic resin emulsion is as follows: The benzotriazole was pretreated by ball milling to obtain modified benzotriazole; 35 parts of methacrylic acid copolymer type B were added to 100 parts of isopropanol and mixed at 45° C., and then 12 parts of the modified benzotriazole were added to the solution and ultrasonically dispersed for 30 minutes.
[0046] Comparative Example 1: This comparative example is based on Example 1. Benzotriazole is not used to modify the methacrylic acid copolymer type B, and 4-pyrazolecarboxylic acid is not used to modify the nano zinc oxide. Instead, benzotriazole and 4-pyrazolecarboxylic acid are directly added to the dispersion containing the methacrylic acid copolymer type B.
[0047] The preparation process of the acrylic resin waterproof coating of this comparative example is as follows: S1, adding 35 parts of methacrylic acid copolymer type B into 100 parts of toluene to obtain a methacrylic acid copolymer solution; S2. Add the methacrylic acid copolymer solution into the stirring tank and stir, then add the dispersant and film-forming agent in sequence and stir at a stirring speed of 600 r.min. -1 ; Make the dispersant and film-forming agent uniformly dispersed in the modified acrylic resin emulsion; S2. Add filler, benzotriazole and 4-pyrazolecarboxylic acid, and continue stirring at a high stirring speed of 1500 r.min. -1 ; Make each component dispersed evenly; S3. Add a thickener to adjust the consistency to about 10 cm to obtain an acrylic resin waterproof coating.
[0048] Comparative Example 2: This comparative example is based on Example 1, and the difference from Example 1 is: The filler was not modified and was directly replaced with an equal amount of nano zinc oxide.
[0049] Comparative Example 3: This comparative example is based on Example 1, and the difference from Example 1 is: The filler was not modified, but directly replaced by nano zinc oxide, and the amount of nano zinc oxide was increased to 50 parts.
[0050] Comparative Example 4: This comparative example is based on Example 1, and the difference from Example 1 is: Nano zinc oxide is modified with silane coupling agent, the specific process is as follows: Add 60 mL of ethanol and 2 g of nano zinc oxide (average particle size 50 nm) into the reaction bottle, perform ultrasonic dispersion treatment, then add 0.4 g of KH550, heat to 60°C, stir and react for 24 hours, centrifuge, wash with ethanol, and dry to obtain KH550 modified zinc oxide.
[0051] Comparative Example 5: This comparative example is based on Example 1, and the difference from Example 1 is: Without using benzotriazole to modify the methacrylic acid copolymer, 35 parts of methacrylic acid copolymer type B were directly added to 100 parts of ethyl acetate for dispersion to obtain a methacrylic acid copolymer solution. That is, the methacrylic acid copolymer solution was used in this comparative example to replace the modified acrylic resin emulsion in Example 1.
[0052] Comparative Example 6: This comparative example is based on Example 1, and the difference from Example 1 is: Without using benzotriazole to modify the methacrylic acid copolymer, 35 parts of methacrylic acid copolymer type B were directly added to 100 parts of toluene for dispersion to obtain a methacrylic acid copolymer solution. That is, in this comparative example, the methacrylic acid copolymer solution was used to replace the modified acrylic resin emulsion in Example 1; and the filler was not modified, but was directly replaced by an equal amount of nano zinc oxide.
[0053] Comparative Example 7: This comparative example is based on Example 1, and the difference from Example 1 is that the preparation process of the modified acrylic resin emulsion is different. The specific preparation process of this comparative example is as follows: 35 parts of methacrylic acid copolymer type B were added to 100 parts of toluene and mixed at room temperature. Then 12 parts of benzotriazole were added to the solution and ultrasonically dispersed for 30 minutes.
[0054] The acrylic resin waterproof coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were subjected to an aging resistance test, wherein the aging time was 168 h, the wavelength of the light source was 340 nm, and the irradiance was 0.76 W / (m 2 ×nm): Refer to the tensile strength and elongation at break of the test of tensile properties of plastics in GB / T1040.1-2018 before and after aging, and calculate Δσ and Δδ, where Δσ is the difference in tensile strength of the coating before and after aging (MPa), and Δδ is the difference in elongation at break of the coating before and after aging (%); the results are shown in Table 1; a 4cm×4cm wooden board is made, and 5mm thick gypsum is first applied on the wooden board. After the gypsum is dried, its surface is polished and flat, and then the acrylic resin waterproof coating prepared in Example 1-Example 3 and Comparative Example 1-Comparative Example 7 is applied on the surface of the gypsum board respectively, and after drying, the dried sample is irradiated with an ultraviolet lamp, the wavelength of the lamp source is 340nm, and the irradiance is 0.76W / (m2 ×nm); after 72h, the color difference ΔE before and after aging was tested. The color difference ΔE was measured with reference to the Lab color space method, and the appearance changes (powdering, cracking) were observed. The results are shown in Table 1.
[0055] Table 1 From the data in Table 1, we can see that: 1) The coating prepared by the present invention uses benzotriazole to modify the methacrylic acid copolymer type B, and uses 4-pyrazolecarboxylic acid to modify the nano zinc oxide as a filler. The appearance of the coating before and after aging has no visible change, and the changes in ΔE (color difference), Δσ (tensile strength difference) and Δδ (elongation at break difference) are all small, ΔE is basically within 0.5, Δσ is within 0.6MPa, and Δδ is within 10%, indicating that the coating prepared in this embodiment has good aging resistance.
[0056] 2) After pretreatment of nano zinc oxide, ΔE (color difference), Δσ (tensile strength difference) and Δδ (elongation at break difference) will be further reduced, indicating that pretreatment of nano zinc oxide is beneficial to improving the aging resistance of the prepared coating. The content of filler in the coating has a certain influence on the aging resistance of the coating. Within a certain range, the higher the content of the coating, the better the aging resistance of the prepared coating.
[0057] 3) Benzotriazole and 4-pyrazolecarboxylic acid were directly added to the methacrylic acid copolymer to prepare the coating. Compared with the modification of the present invention, ΔE (color difference), Δσ (tensile strength difference) and Δδ (elongation at break difference) were greatly improved. The reason may be that direct addition did not achieve the modification effect.
[0058] 4) Compared with unmodified nano zinc oxide, the addition of nano zinc oxide modified with 4-pyrazolecarboxylic acid to the paint can greatly improve the aging resistance of the paint. When nano zinc oxide is used as a filler in the paint, when the filler reaches a certain amount, the aging resistance of the paint cannot be improved by increasing the amount of filler; on the contrary, excessive use of the paint will lead to powdering and cracking after aging.
[0059] 5) Using the silane coupling agent in the prior art to modify the nano zinc oxide cannot improve the aging resistance of the coating by modifying the filler.
[0060] 6) Failure to use benzotriazole-modified methacrylic acid copolymer will lead to reduced aging resistance of the coating; failure to use benzotriazole-modified methacrylic acid copolymer; and failure to use 4-pyrazolecarboxylic acid-modified nano zinc oxide will further reduce the aging resistance of the coating.
[0061] 7) During the preparation process of the coating of the present invention, whether benzotriazole is pretreated by ball milling also has a certain influence on the aging resistance of the coating.
[0062] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An aging-resistant acrylic resin waterproof coating, characterized in that: It includes the following components by weight: 100 parts of modified acrylic resin emulsion, 30-40 parts of filler, 5-8 parts of film former, 2-3 parts of thickener, 2-3 parts of dispersant; Wherein, the modified acrylic resin emulsion comprises a methacrylic acid copolymer, and the methacrylic acid copolymer contains an ultraviolet absorber; Wherein, the filler is nano-oxide particles modified with 4-pyrazolecarboxylic acid, and the nano-oxide particles include at least one of nano-zinc oxide and nano-titanium dioxide.
2. The aging-resistant acrylic resin waterproof coating according to claim 1, characterized in that: The ultraviolet absorber includes benzotriazole.
3. The aging-resistant acrylic resin waterproof coating according to claim 1, characterized in that: The benzotriazole is pretreated by ball milling.
4. The aging-resistant acrylic resin waterproof coating according to claim 1, characterized in that: The preparation process of the filler is as follows: The 4-pyrazolecarboxylic acid is added to 85% ethanol, and ultrasonic dispersion is performed for 20-30 minutes. Then, the nano-oxide particles are added to the solution, and ultrasonic dispersion is performed for 40-60 minutes. Then, the ethanol is volatilized and air-dried to obtain the filler.
5. The aging-resistant acrylic resin waterproof coating according to claim 4, characterized in that: The weight ratio of the ethanol, the nano-oxidation particles and the 4-pyrazolecarboxylic acid is (10-15): (8-12): (3-5).
6. The aging-resistant acrylic resin waterproof coating according to claim 5, characterized in that: The weight ratio of the ethanol, the nano-oxidation particles and the 4-pyrazolecarboxylic acid is 15:10:(3-5).
7. The aging-resistant acrylic resin waterproof coating according to claim 4, characterized in that: The nano-oxide particles are first pretreated: The nano-oxide particles are dispersed in a sodium chloride solution, wet-milled, and dried.
8. The method for preparing the acrylic resin waterproof coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, adding the modified acrylic resin emulsion into a stirring tank and stirring, then sequentially adding the dispersant and the film-forming agent, stirring, so that the dispersant and the film-forming agent are uniformly dispersed in the modified acrylic resin emulsion; S2, adding the filler, and continuing stirring at a high stirring speed to make the components dispersed evenly; S3, adding the thickener to adjust the consistency to obtain the acrylic resin waterproof coating.
9. The preparation method according to claim 8, characterized in that: In step S1, the stirring speed is 500-600 r.min -1 .
10. The preparation method according to claim 8, characterized in that: In step S2, the stirring speed is 1500-1600 r.min -1 .
Citation Information
Patent Citations
High-solid epoxy zinc-rich paint and preparation method thereof
CN118834579A
Preparation method of anticorrosive coating based on modified acrylic resin
CN118978862A
Nano UV resistant acrylate paint
CN1412258A